PENGARUH RASIO AKTIVITAS, EFISIENSI OPERASIONAL, DAN TINGKAT SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR PROPERTI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2023 - Ni Ketut Poni Ulandari; Nyoman Ayu Wulan Trisna Dewi (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aimed to thoroughly examine the influence of activity ratio (TATO), operational efficiency (BOPO), and solvency level (DER) on the profitability (ROA) of property sector companies listed on the Indonesia Stock Exchange (IDX) during the period from 2020 to 2023. The research employed a quantitative method with a sample of 26 companies selected through purposive sampling out of a total of 94 listed companies. Data were obtained from published annual financial reports and analysed using multiple regression techniques to assess the impact of each variable. The results indicate that the activity ratio (TATO) and the solvency level (DER) have a positive and significant effect on profitability, whereas operational efficiency (BOPO) does not show a significant influence. These findings reinforce the importance of effective asset and debt management to improve efficiency and the sustainability of financial performance in property companies, especially in challenging market conditions. The results of this study are expected to provide empirical evidence that can serve as a foundation for future research related to the influence of solvency on the profitability of companies in the property sector, thereby enriching the literature and expanding the understanding of financial factors that impact profitability.